Clinical and radiographical evaluation of the tricalcium silicate (Biodentine)® used in pulpotomy of primary molars. Case report - Jara - Porroa, Jackeline Jajaira (2020)
Biodentine®, induces the development of reparative dentin and achieves the maintenance of tissue vitality and function, thus avoiding more invasive treatments such as pulpectomies or extractions. Objective: To describe the clinical and radiographic behavior of the pulp exposed to tricalcium silicate(Biodentine®) used in pulpotomies as a treatment of deciduous molars.Results: The evaluations of 3, 6 and 9 months showed clinical and radiographic success of all the procedures.Conclusions: It was evidenced that Biodentine® can be used or considered an effective and promising medicinein treatment of pulpotomies in deciduous teeth. However, more long-term clinical studies are needed tohave more accurate conclusions.